Effects of high intensity training on mitochondrial function in subcutaneous adipose tissue and skeletal muscle - Larsen, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
In the last couple of years high intensity training (HIT) has again been studied intensively. HIT has been shown to increase maximal oxygen uptake (VO2max) and skeletal muscle mitochondrial oxidative phosphorylation (OXPHOS) capacity in young male subjects. Furthermore it has also been reported that HIT improves glucose tolerance in young subjects, this effect could potentially be via a reduction in reactive oxygen species (ROS) production from the skeletal muscle, but this has never been investigated after HIT before. The literature is sparse, when it comes to HIT in older females and males. Furthermore mitochondrial respiratory capacity has not been investigated after HIT in subcutaneous adipose tissue previously. During the talk it will be discussed if the effect of HIT is similar between young and old subjects when it comes to mitochondrial respiratory capacity. Furthermore it will also be discussed if HIT improves glucose tolerance in a similar way as endurance training, and if this potential improvement can be linked to an improved ROS level in the skeletal muscle.